Dysbiosis From a Microbial and Host Perspective Relative to Oral Health and Disease - Cugini, Carla; Ramasubbu, Narayanan; Tsiagbe, Vincent K.; Fine, Daniel H. (Frontiers in Microbiology, 2021)
The significance of microbiology and immunology with regard to caries and periodontal disease gained substantial clinical or research consideration in the mid 1960’s. This enhanced emphasis related to several simple but elegant experiments illustrating the relevance of bacteria to oral infections. Since that point, the understanding of oral diseases has become increasingly sophisticated and many of the original hypotheses related to disease causality have either been abandoned or amplified. The COVID pandemic has reminded us of the importance of history relative to infectious diseases and in the words of Churchill “those who fail to learn from history are condemned to repeat it”. This review is designed to present an overview of broad general directions of research over the last 60 years in oral microbiology and immunology, reviewing significant contributions, indicating emerging foci of interest, and proposing future directions based on technical advances and new understandings. Our goal is to review this rich history (standard microbiology and immunology) and point to potential directions in the future (omics) that can lead to a better understanding of disease. Over the years, research scientists have moved from a position of downplaying the role of bacteria in oral disease to one implicating bacteria as true pathogens that cause disease. More recently it has been proposed that bacteria form the ecological first line of defense against “foreign” invaders and also serve to train the immune system as an acquired host defensive stimulus. While early immunological research was focused on immunological exposure as a modulator of disease, the “hygiene hypothesis”, and now the “old friends hypothesis” suggest that the immune response could be trained by bacteria for long-term health. Advanced “omics” technologies are currently being used to address changes that occur in the host and the microbiome in oral disease. The ‘omics’ methodologies have shaped the detection of quantifiable biomarkers to define human physiology and pathologies. In summary, this review will emphasize the role that commensals and pathobionts play in their interaction with the immune status of the host, with a prediction that current “omic” technologies will allow researchers to better understand disease in the future.